Dietary phytate primes epithelial antibacterial immunity in the intestine - Hashimoto-Hill, Seika; Colapietro, Luisa; Woo, Vivienne; Antonacci, Simona; Whitt, Jordan; Engleman, Laura; Alenghat, Theresa (Frontiers in Immunology, 2022)
Although diet has long been associated with susceptibility to infection, the dietary components that regulate host defense remain poorly understood. Here, we demonstrate that consuming rice bran decreases susceptibility to intestinal infection with Citrobacter rodentium, a murine pathogen that is similar to enteropathogenic E. coli infection in humans. Rice bran naturally contains high levels of the substance phytate. Interestingly, phytate supplementation also protected against intestinal infection, and enzymatic metabolism of phytate by commensal bacteria was necessary for phytate-induced host defense. Mechanistically, phytate consumption induced mammalian intestinal epithelial expression of STAT3-regulated antimicrobial pathways and increased phosphorylated STAT3, suggesting that dietary phytate promotes innate defense through epithelial STAT3 activation. Further, phytate regulation of epithelial STAT3 was mediated by the microbiota-sensitive enzyme histone deacetylase 3 (HDAC3). Collectively, these data demonstrate that metabolism of dietary phytate by microbiota decreases intestinal infection and suggests that consuming bran and other phytate-enriched foods may represent an effective dietary strategy for priming host immunity.